Hepatic Steatosis Is Associated with High White Blood Cell and Platelet Counts - Yu-Lin Chao; Pei-Yu Wu; Jiun-Chi Huang; Yi-Wen Chiu; Jia-Jung Lee; Szu-Chia Chen; Jer-Ming Chang; Shang-Jyh Hwang; Hung-Chun Chen (Biomedicines, 2022)
The incidence of hepatic steatosis is increasing globally, and it is important to identify those at risk to prevent comorbidities. Complete blood count is a simple, convenient, and inexpensive laboratory examination which can be used to obtain white blood cell (WBC) and platelet counts. The aims of this study were to investigate the relationships between WBC and platelet counts with hepatic steatosis, and whether WBC and platelet counts were associated with the severity of hepatic steatosis. We enrolled 1969 participants residing in southern Taiwan who took part in a health survey from June 2016 to September 2018 in this cross-sectional study. None of the participants were heavy alcohol users or had a history of hepatitis B or C. We collected laboratory data, and the severity of hepatic steatosis was determined by abdominal ultrasound. The overall prevalence rate of hepatic steatosis was 42.0%. There were significant trends of stepwise increases in WBC count (p < 0.001) corresponding to the severity of hepatic steatosis. After multivariable linear regression analysis, hepatic steatosis was significantly associated with high WBC count (coefficient β, 0.209; 95% confidence interval (CI), 0.055 to 0.364; p = 0.008) and high platelet count (coefficient β, 12.213; 95% CI, 6.092 to 18.334; p < 0.001); also, higher WBC counts corresponded with the severity of hepatic steatosis.